Answer:
14 x^5 - 21 x^4 - 266 x^3 - 315 x^2
Step-by-step explanation:
Expand the following:
7 x^2 (2 x + 5) (x^2 - 4 x - 9)
| | | | 2 x | + | 5
| | x^2 | - | 4 x | - | 9
| | | | -18 x | - | 45
| | -8 x^2 | - | 20 x | + | 0
2 x^3 | + | 5 x^2 | + | 0 | + | 0
2 x^3 | - | 3 x^2 | - | 38 x | - | 45:
7 x^2 2 x^3 - 3 x^2 - 38 x - 45
7 x^2 (2 x^3 - 3 x^2 - 38 x - 45) = 7 x^2 (2 x^3) + 7 x^2 (-3 x^2) + 7 x^2 (-38 x) + 7 x^2 (-45):
7 2 x^2 x^3 - 3 7 x^2 x^2 - 38 7 x^2 x - 45 7 x^2
7 (-45) = -315:
7 2 x^2 x^3 - 3 7 x^2 x^2 - 38 7 x^2 x + -315 x^2
7 x^2 (-38) x = 7 x^(2 + 1) (-38):
7 2 x^2 x^3 - 3 7 x^2 x^2 + -38×7 x^(2 + 1) - 315 x^2
2 + 1 = 3:
7 2 x^2 x^3 - 3 7 x^2 x^2 - 38 7 x^3 - 315 x^2
7 (-38) = -266:
7 2 x^2 x^3 - 3 7 x^2 x^2 + -266 x^3 - 315 x^2
7 x^2 (-3) x^2 = 7 x^4 (-3):
7 2 x^2 x^3 + -3×7 x^4 - 266 x^3 - 315 x^2
7 (-3) = -21:
7 2 x^2 x^3 + -21 x^4 - 266 x^3 - 315 x^2
7 x^2×2 x^3 = 7 x^(2 + 3)×2:
7×2 x^(2 + 3) - 21 x^4 - 266 x^3 - 315 x^2
2 + 3 = 5:
7 2 x^5 - 21 x^4 - 266 x^3 - 315 x^2
7×2 = 14:
Answer: 14 x^5 - 21 x^4 - 266 x^3 - 315 x^2